Duration of balloon inflation for optimal stent deployment: Five Seconds Is Not Enough. Issue 3 (10th January 2012) - Hovasse, Thomas; Mylotte, Darren; Garot, Philippe; Salvatella, Neus; Morice, Marie‐Claude; Chevalier, Bernard; Pichard, Augusto; Lefèvre, Thierry
<x xml:space="preserve">Abstract</x> Objectives: To assess the effect of the duration of stent inflation on stent expansion using digital stent enhancement (DSE). Background: Optimal stent expansion and apposition to the vessel wall are of critical importance to optimize the results of percutaneous coronary intervention (PCI). However, it is not known if stent inflation duration impacts on stent expansion. Methods: We performed a prospective cohort study in patients undergoing PCI. Quantitative coronary angiography and DSE data were analyzed. DSE was performed at 5, 15, and 25 sec during stent implantation, after target balloon inflation pressure was achieved. Results: One hundred and four consecutive patients (150 lesions) were enrolled. The mean age was 66.9 ± 11.1 years. Complex lesions (ACC/AHA B2/C) occurred in 26.9%. Stents used: Cypher Select (54.1%), Xience V (30.6%), and Taxus Liberté (15.3%). The minimal stent diameter increased significantly with the duration of stent inflation: 2.60 ± 0.51, 2.76 ± 0.51, and 2.82 ± 0.52 mm at 5, 15, and 25 sec (P < 0.0001). Similarly, maximal stent diameter increased with the duration of stent inflation: 3.21 ± 0.51, 3.32 ± 0.52, and 3.36 ± 0.54 mm (P < 0.0001). The average stent diameter also increased with longer stent inflation (P < 0.0001). Using MUSIC criteria 24.0, 53.3, and 68.0% of stents were appropriately expanded at 5, 15, and 25 sec (P < 0.0001).Conclusions: The duration of stent balloon inflation has a significant impact on stent expansion. Stent deployment for >25 sec is recommended. © 2012 Wiley Periodicals, Inc.